The Effect Of The Viral Marketing Song On The Millenial Generation’s Buying Interest - Husnusyifa, Annisa; Mujianto, Haryadi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2023)
This research was motivated by a jazz singer named Tulus from Bandung, whose song went viral in March 2022. “Hati-Hati di Jalan” managed to occupy the 42 Global Top 50 on Spotify. This indicates that the song is worldwide and enjoyed by global listeners, including the millennial generation. According to Chart Data, the Indonesian song managed to become the first in history to occupy that position. The presence of viral marketing can also help Spotify to introduce its songs more effectively, massively and quickly to the millennial generation. The purpose of this study was to find out how high the influence of viral marketing for the song "Hati Hati di Jalan" by Tulus on the Spotify application on the millennial generation's buying interest on Instagram. This study uses a quantitative approach based on the philosophy of positivism. The analytical technique used is simple linear regression which is processed using the SPSS Statistic version 27 program. The results of this study indicate that the high influence of viral marketing for the song "Hati Hati di Jalan" by Tulus on the Spotify application on the millennial generation's buying interest on Instagram is 54.6%, while the remaining 45.4% is influenced by other variables not examined in this study.